IMPLIKASI IN-HOUSE TRAINING KEMENTERIAN AGAMA TERHADAP PENJAMINAN MUTU PENDIDIKAN DI MADRASAH ALIYAH AL-MUHAJIRIN PANDAN - Atikah Putri Dinanty; Wahab Wahab (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the implications of the Ministry of Religious Affairs’ In-House Training (IHT) program on educational quality assurance at MA Al-Muhajirin Pandan, Sintang Regency, West Kalimantan. The study employs a qualitative approach using a single-case study design. Data were collected through semi-structured interviews with four informants. Data analysis utilized the interactive model by Miles, Huberman, and Saldaña, along with the Kirkpatrick Four-Level Evaluation Model as an analytical framework. The research results revealed four tiered findings: first, teachers’ responses to the IHT were generally positive, although accompanied by critical remarks regarding variations in the quality of facilitation; second, the IHT produced more profound changes in competencies among teachers who participated in direct training compared to those who acquired knowledge through internal socialization; third, the transfer of IHT outcomes to classroom practice occurred selectively, with work environment factors serving as the strongest determinant; fourth, IHT contributed to institutional quality assurance through the development of the KOM. The novelty of this study lies in the longitudinal analysis of the chain of implications of IHT in rural private madrasah aliyah that operate without a formal SPMI, a context that has never been examined within an integrated theoretical framework.